Non-adherence to Thromboprophylaxis Guidelines in Atrial Fibrillation: A Narrative Review of the Extent of and Factors in Guideline Non-adherence - Gebreyohannes, Eyob Alemayehu; Salter, Sandra; Chalmers, Leanne; Bereznicki, Luke; Lee, Kenneth (Springer, 2020)
Atrial fibrillation is the most common arrhythmia. It increases the risk of thromboembolism by up to fivefold. Guidelines provide evidence-based recommendations to effectively mitigate thromboembolic events using oral anticoagulants while minimizing the risk of bleeding. This review focuses on non-adherence to contemporary guidelines and the factors associated with guideline non-adherence. The extent of guideline non-adherence differs according to geographic region, healthcare setting, and risk stratification tools used. Guideline adherence has gradually improved over recent years, but a significant proportion of patients are still not receiving guideline-recommended therapy. Physician-related and patient-related factors (such as patient refusals, bleeding risk, older age, and recurrent falls) also contribute to guideline non-adherence, especially to undertreatment. Quality improvement initiatives that focus on undertreatment, especially in the primary healthcare setting, may help to improve guideline adherence.